The impact of divorce on the social emotional development of early children - Latifah, Aeni; Anisak Nurul Fitri, Dwi; Nur Afriliani, Ajeng Teni; Awalia Farida, Neng (IKIP Siliwangi, 2025)
Parental care is one of the factors that influences children's social emotional development. However, quite a few children do not experience complete care from both parents because of divorce. Divorce itself is a condition where the two parents have to separate and force the child to be raised only by one of the parents, father or mother, raised by relatives or even by other people. This research is a literature study by collecting various information from books and journal articles that are relevant to the problem topic under study, namely related to the impact of divorce on the social emotional development of early childhood. The research results show that divorce can have a significant impact on children, especially their social emotional development. Negatively, children who are victims of divorce are more likely to experience anxiety, stress, behavioral and emotional problems, as well as difficulties in building social relationships. However, with support from the surrounding environment, such as teachers, extended family and the community, we can minimize and overcome the negative impact caused by the divorce of parents. Apart from that, the support of parents who are not conflicted and have good relationships can provide affection, communication and maintain the stability of children during the transition period. A factor that is quite good for the social emotional development of children who are victims of divorce.